The Inflation Expectations of U.S. Firms: Evidence from a New Survey - Bernardo Candia; Olivier Coibion; Yuriy Gorodnichenko (Institute of Labor Economics (IZA), 2021)
Introducing a new survey of U.S. firms' inflation expectations, we document key stylized facts involving what U.S. firms know and expect about inflation and monetary policy. The resulting time series of firms' inflation expectations displays unique dynamics, distinct from those of households and professional forecasters. By any typical definition of "anchored" expectations, the inflation expectations of U.S. managers appear far from anchored, much like those of households. And like households, U.S. managers are largely uninformed about recent aggregate inflation dynamics or monetary policy. These results complement existing evidence on firms' inflation expectations from other countries and confirm that inattention to inflation and monetary policy is pervasive among U.S. firms as well.
Keywords: E3; E4; E5; 330; expectations; surveys; anchoring; rational inattention